Workspace Analysis of a Hybrid Kinematic Machine Tool with High Rotational Applications. (26th June 2018) - Zhang, Haiqiang; Fang, Hairong; Fang, Yuefa; Jiang, Bingshan
Abstract : This paper presents a novel parallel manipulator with one translational and two rotational (1T2R) degrees of freedom that can be employed to form a five-degree-of-freedom hybrid kinematic machine tool for large heterogeneous complex structural component machining in aerospace field. Compared with serial or parallel machine, hybrid machine has the merits of high stiffness, high speed, large workspace, and complicated surface processing ability. To increase stiffness, three-degree-of-freedom redundantly actuated and overconstrained 2P RU-P RP S parallel manipulator (P denotes the active prismatic joint) is proposed, which is utilized as the main body of hybrid machine. By resorting to the screw theory, the degree of freedom of the proposed mechanism is briefly addressed including the initial configuration and general configuration and validated by Grübler-Kutzbach (G-K) equation. Next, kinematic inverse solution and parasitic motion of the parallel manipulator are deduced and the transformational relations between the Euler angle and Tilt-Torsion (T-T) angle are identified. Thirdly, the performance evaluation index of orientation workspace is introduced, and the reachable workspace and joint workspace are formulated. Through specific examples, the reachable workspace, task workspace, and joint workspace of the redundant actuation parallel manipulator are depicted. Compared with overstrained 2PRU-PRS parallel manipulator, corresponding analyses illustrate that the proposed parallel manipulator owns much better orientation capability and is very meaningful to the development of the five-axis hybrid machine tool.